Natronoglomus mannanivorans gen. nov., sp. nov., beta-1,4-mannan utilizing natronoarchaea from hypersaline soda lakes - Sorokin, Dimitry Y.; Elcheninov, Alexander G.; Bale, Nicole J.; Sinninghe Damsté, Jaap S.; Kublanov, Ilya V. (Frontiers in Microbiology, 2024)
Beta-mannans are insoluble plant polysaccharides with beta-1,4-linked mannose as the backbone. We used three forms of this polysaccharide, namely, pure mannan, glucomannan, and galactomannan, to enrich haloarchaea, which have the ability to utilize mannans for growth. Four mannan-utilizing strains obtained in pure cultures were closely related to each other on the level of the same species. Furthermore, another strain selected from the same habitats with a soluble beta-1,4-glucan (xyloglucan) was also able to grow with mannan. The phylogenomic analysis placed the isolates into a separate lineage of the new genus level within the family Natrialbaceae of the class Halobacteria. The strains are moderate alkaliphiles, extremely halophilic, and aerobic saccharolytics. In addition to the three beta-mannan forms, they can also grow with cellulose, xylan, and xyloglucan. Functional genome analysis of two representative strains demonstrated the presence of several genes coding for extracellular endo-beta-1,4-mannanase from the GH5_7 and 5_8 subfamilies and the GH26 family of glycosyl hydrolases. Furthermore, a large spectrum of genes encoding other glycoside hydrolases that were potentially involved in the hydrolysis of cellulose and xylan were also identified in the genomes. A comparative genomics analysis also showed the presence of similar endo-beta-1,4-mannanase homologs in the cellulotrophic genera Natronobiforma and Halococcoides. Based on the unique physiological properties and the results of phylogenomic analysis, the novel mannan-utilizing halolarchaea are proposed to be classified into a new genus and species Natronoglomus mannanivorans gen. nov., sp. nov. with the type strain AArc-m2/3/4 (=JCM 34861=UQM 41565).